1976
DOI: 10.1111/j.1471-0528.1976.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

MEASUREMENT OF INTERVILLOUS AND MYOMETRIAL BLOOD FLOW BY AN INTRAVENOUS 133Xe METHOD

Abstract: A new 'non-invasive' method for measuring intervillous and myometrial blood flow is presented. After 2 mCi of 133Xe in physiological saline was injected intravenously the patient held her breath for 20 seconds. The tracer entered the placenta as a short bolus and its removal was followed with a scintillation detector. Intervillous and myometrial blood flow per unit volume was calculated from the two-exponential curve. The mean &SD intervillous flow in normal pregnancy was 135 f49 ml/minute/100 ml, the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…These patients remained in the tilted left laterally position from PCB until the second measurement. The placental blood flow in ml/min/100 ml of the intervillous space was measured by 133 Xe-washout method described in detail elsewhere [15].…”
Section: Uterine Activitymentioning
confidence: 99%
“…These patients remained in the tilted left laterally position from PCB until the second measurement. The placental blood flow in ml/min/100 ml of the intervillous space was measured by 133 Xe-washout method described in detail elsewhere [15].…”
Section: Uterine Activitymentioning
confidence: 99%
“…In recent years the vasculature of the human uterus has been well studied, moving from the static picture of injection techniques (Lundgren, 1957) to more recent rheometric methods using radioactive isotopes (Rekonen et al, 1976). Boving (1962) demonstrated that the apposition of an endometrial end-artery to the trophoblast knob is critical in the formation of placental cotyledons.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ex amination techniques suited for evaluating these parameters are of vital clinical interest. In clinical routine uteroplacental blood flow can only be measured by using radionuclide methods with intravenous tracer application [8,9], But these have limited diagnostic po tential, because they furnish no more than qualitative data on uteroplacental blood flow and cannot be repeated within a short inter val. Earlier studies have, however, shown the results obtained with the technique of blood flow measurement practiced by us to be of outstanding clinical relevance [8].…”
Section: Discussionmentioning
confidence: 99%